Outcome of therapeutic penetrating keratoplasty in a tertiary eye care center in Nepal - Bajracharya L (Dove Medical Press, 2015)
Leena Bajracharya, Reeta Gurung Department of Cornea, Tilganga Institute of Ophthalmology, Kathmandu, Nepal Background: Corneal ulcer is an important cause of blindness in developing countries. Therapeutic keratoplasty for infective keratitis is a frequently performed surgery in these countries.Objective: To find out the outcome of therapeutic keratoplasty for infective keratitis.Methods: Records of 5 years were reviewed of patients who underwent therapeutic keratoplasty from 2006 to 2010. Data collected included demographic parameters, indications for surgery, microbiology of the ulcers, type of surgery performed, and donor tissue details. In the follow-up period, ocular status was evaluated in terms of eradication of disease, anatomic success, graft clarity, visual acuity, and development of glaucoma and cataract.Results: In all, 180 eyes of 180 patients were enrolled in the study; 59.4% of the patients were male. Average age was 44.4±16.7 years. Overall, 71% of infective keratitis was perforated. A total of 101 (56%) eyes were positive for organisms of which 49 showed pure fungus and 49 showed pure bacteria. The commonest fungus and bacteria isolated were Aspergillus and Streptococcus, respectively. Average follow-up period was 29±23 months. Overall cure rate of infection was 88.8%, anatomical success rate was 89.5%, and graft clarity was 37.2%. Overall, 43.4% had secondary glaucoma. In the postoperative course, 65.8% of phakic eyes had developed cataract. In all, 38.6% of graft had endothelial failure and 24% of the graft failed due to late infective keratitis. Overall functional success with a visual acuity above 6/60 was 25.4%. Bacterial keratitis had a significantly higher cure rate, anatomical success, and graft clarity compared to fungal keratitis.Conclusion: Therapeutic keratoplasty is an important procedure to save the eye and preserve vision in severe infective keratitis. There is a high incidence of postoperative glaucoma, cataract, and graft failure in such a surgery. Bacterial keratitis has a better outcome than fungal keratitis. Keywords: therapeutic penetrating keratoplasty, infective keratitis, Nepal, corneal ulcer